Incentive contracts with unobservable competence levels - Jerome Davis; Hans Keiding (The Open Economics Journal, 2008)
A contract where the agent is compensated ex post only upon satisfactory performance, often called a no-cureno-pay contract, can arise as under several circumstances. In this paper, we model the problem of contractual choice as a principal-agent contract which is modified due to hidden information about the competence of the agent to fulfill the obligations of the contract. The agent offers a choice of contracts to the principal, thereby signalling agent competence to the principal, and there is no alternative reputation mechanism to the contract for the principal's bargaining strategy. It turns out that in this situation, the optimal contract will have a form which may be recognized as a no-cure-no-pay contract.
Keywords: 330; contracts; no-cure-no-pay; principal-agent model; asymmetric information